The impact of political connections on cost of funding and bank performance of foreign exchange national bank - Muazaroh Muazaroh; Indra Listyarti; Indah Wahyu Rusdianawati (Manajemen dan Bisnis, 2022)
Political connection is an expensive resource that can be a source of competitive advantage for a bank. Banks that have political connections will be able to get funding at a lower cost because depositors feel that their funds are safe. The existence of low funding costs will have an impact on better bank performance. This study aims to examine the effect of political connections on bank funding costs and bank performance. The research sample uses 28 foreign exchange banks in Indonesia in the 2014-2017 period which are divided into politically connected and politically unconnected banks. The results show that politically connected banks have cheaper funding costs and better performance than banks that are not politically connected. The implication of this research for banking institutions is that political connections are an advantage that can be used to obtain funds from the public at a lower cost and will be able to improve bank performance.